건강보험가입자의 의료급여 자격변동에 따른 의료이용행태 변화 연구 - 나영균; Young-kyoon Na; 차예린; Yerin Cha; 김나영; Nayoung Kim; 이영재; Youngjae Lee; 이용갑; Yong-gab Lee; 임승지; Seungji Lim (Health policy and management, 2020)
Background: The purpose of this study is to analyze whether there is a change in patterns of medical use among those likely to be converted their health insurance qualifications when the family support rule is alleviated. There is no empirical analysis that converting health insurance qualification will affect the increase in medical use. Methods: For analysis, data were extracted from the national health insurance eligibility and medical care database. To identify analysis targets similar to that of medical aids’ characteristics among health insurance coverage, we compared income, property level, and medical use patterns through basic statistical analysis and used a difference-in-difference (DID) analysis to estimate the net effect of changes in medical use following the change of qualifications. Results: The main results are as follows. The results show that those who are under the 5% income group (1st income group) of health insurance coverage are the most similar to the medical aids group. DID analysis shows that changes in the medical use of people who maintain their national insurance qualification and who are not. As a results, the number of hospitalized days of converting group was reduced by 3.5 days while outpatient days were increased by 1.8 days. Conclusion: As a result, there was not much difference in the patterns of medical use for the under 5% income group who are likely to be eligible for expanded medical aids when the family support rule is alleviated. In addition, more than 30% of them are in arrears with their health insurance premiums, causing inconvenience in using medical services. These findings suggest the need of abolishing the criteria obligated to support family, and great efforts should be made to contribute to non-paid poor and remove their medical blind spot.